Clostridium difficile PCR Ribotype 018, a Successful Epidemic Genotype - Baldan, Rossella (J Clin Microbiol, 2015)
Clostridium difficile infection (CDI) became a public health problem for the global spreading of the so-called hypervirulent PCR ribotypes (RTs) 027 and 078, associated with increases in the transmission and severity of the disease. However, especially in Europe, several RTs are prevalent, and the concept of hypervirulence is currently debated. We investigated the toxin and resistance profiles and the genetic relatedness of 312 C. difficile strains isolated in a large Italian teaching hospital during a 5-year period. We evaluated the role of CDI-related antibiotic consumption and infection control practices on the RT predominance in association with their molecular features and transmission capacity. Excluding secondary cases due to nosocomial transmission, RT018 was the predominant genotype (42.4%) followed by RT078 (13.6%), while RT027 accounted for 0.8% of the strains. RT078 was most frequently isolated from patients in intensive care units. Its prevalence significantly increased over time, but its transmission capacity was very low. In contrast, RT018 was highly transmissible and accounted for 95.7% of the secondary cases. Patients with the RT018 genotype were significantly older than those with RT078 and other RTs, indicating an association between epidemic RT and age. We provide here the first epidemiological evidence to consider RT018 as a successful epidemic genotype that deserves more attention in clinical practice.